Autonomic Nervous System Responses During Perception of Masked Speech may Reflect Constructs other than Subjective Listening Effort - Francis, Alexander L.; MacPherson, Megan K.; Chandrasekaran, Bharath; Alvar, Ann M. (Frontiers in Psychology, 2016)
Typically, understanding speech seems effortless and automatic. However, a variety of factors may, independently or interactively, make listening more effortful. Physiological measures may help to distinguish between the application of different cognitive mechanisms whose operation is perceived as effortful. In the present study, physiological and behavioral measures associated with task demand were collected along with behavioral measures of performance while participants listened to and repeated sentences. The goal was to measure psychophysiological reactivity associated with three degraded listening conditions, each of which differed in terms of the source of the difficulty (distortion, energetic masking, and informational masking), and therefore were expected to engage different cognitive mechanisms. These conditions were chosen to be matched for overall performance (keywords correct), and were compared to listening to unmasked speech produced by a natural voice. The three degraded conditions were: (1) Unmasked speech produced by a computer speech synthesizer, (2) Speech produced by a natural voice and masked by speech-shaped noise and (3) Speech produced by a natural voice and masked by two-talker babble. Masked conditions were both presented at a -8 dB signal to noise ratio (SNR), a level shown in previous research to result in comparable levels of performance for these stimuli and maskers. Performance was measured in terms of proportion of key words identified correctly, and task demand or effort was quantified subjectively by self-report. Measures of psychophysiological reactivity included electrodermal (skin conductance) response frequency and amplitude, blood pulse amplitude and pulse rate. Results suggest that the two masked conditions evoked stronger psychophysiological reactivity than did the two unmasked conditions even when behavioral measures of listening performance and listeners’ subjective perception of task demand were comparable across the three degraded conditions.